CURVES AND SURFACES IN COMPUTER GRAPHICS, THEIR PROFITABILITY - Mamurova Feruza Islomovna; Xodjaeva Nodira Sharifovna (PEDAGOGS, 2025)
Annotation. The class of a plane curve is determined by the number of attempts made on it from an arbitrary point of that plane, and computer graphics the class of a spatial curve is determined by the number of urinal planes passed to it through some straight line.